Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)
Publisher: Les Presses de l’Université de Montréal

Maryvonne Kendergi. La musique en partage - Bail, Louise (Éditions Hurtubise, 2002)

L’apport de Maryvonne Kendergi à la SMCQ - Bail, Louise (Circuit : musiques contemporaines, 2017)
To measure Maryvonne Kendergi’s contributions to the smcq, it is necessary to revisit her career in Quebec, which was based on the solid academic and professional training she received at Parisian institutions from 1929 to 1952. Thereafter, in Montreal, she was hired by Radio-Canada for her exceptional voice, and in September 1956, she embarked on a brilliant radio career as a promoter of contemporary music. Kendergi gradually introduced the listening public to the arcana of the Montreal avant-garde. In this endeavour she was encouraged by Stockhausen’s arrival in Montreal in 1958, by composers’ efforts in organizing International Music Week in 1961, by the foundation of the smcq in 1966, and by the influence of the latter organization, particularly in its collaboration with the Université de Montréal in establishing the Musialogues in 1969. The role of Kendergi’s exceptional skills in broadening the influence of the smcq is explored in this article.
Publisher: Circuit, musiques contemporaines
Keywords: Maryvonne Kendergi; Musialogues; Société de musique contemporaine du Québec (smcq); animatrice; host; music journalist; musicographe de radio

La SQRM 1980-2005 : Une première approche historique - Bail, Louise (Les Cahiers de la Société québécoise de recherche en musique, 2020)
En 2005, l’ARMuQ/SQRM fêtait son 25 e anniversaire d’existence. Répondant aux questions de la rédactrice en chef des présents Cahiers , Sylvia L’Écuyer, l’auteure expose d’abord les motifs qui ont poussé les membres fondateurs à créer ce qui s’appelait alors l’Association pour l’avancement de la recherche en musique du Québec (ARMuQ). Cette section est suivie d’un aperçu des différentes phases de l’évolution de l’association. Enfin, dans une troisième section intitulée « Problématiques et souhaits d’avenir », Louise Bail tente de dégager très brièvement les liens que l’ARMuQ/SQRM a développés avec les institutions d’enseignement supérieur et de circonscrire la place que prennent les chercheurs indépendants au sein de l’organisme. Son propos s’emploie à faire ressortir les problèmes particuliers que posent le fonctionnement et l’existence d’une telle association. Enfin, elle propose des réflexions et suggère quelques pistes d’avenir à partir de son implication en tant que membre fondateur, membre régulier et présidente sortante du conseil d’administration. , In 2005, the ARMuQ/SQRM celebrated its twenty-fifth anniversary. Responding to questions from the Cahier’s current Editor-in-Chief, Sylvia L’Écuyer, the author begins by discussing the motives that gave rise to the Association pour l’avancement de la recherche en musique du Québec, as it was then called. This is followed by a survey of the association’s various transformations over the years. In a third section entitled “Problématiques et souhaits d’avenir” (“Challenges and wishes for the future”), Louise Bail describes the ties that bind the ARMuQ/SQRM to post-secondary education institutions, and identifies the role of independent scholars within the organisation. The aim of her study is to discern the particular challenges that the existence and operations of such an association create. Finally, she reflects and advises on the association’s future from the perspective of her own role as founding member, regular member, and past Chair of the Board of Directors.